2019
DOI: 10.2478/sjdv-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology and risk factors of syphilis in Makassar, Indonesia

Abstract: Introduction. Syphilis is an infectious disease caused by Treponema pallidum spirochete and is mainly transmitted by sexual contact. Syphilis has the potential to cause serious complications and is closely related to human immunodeficiency virus (HIV) infection thus making syphilis still a major public health problem. In Indonesia, surveys of high-risk populations in 2007 and 2011 reported an increase in the prevalence of syphilis, especially in men who have sexual relationships with other men (MSM). Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Of the 220 patients diagnosed with secondary syphilis in Indonesia, the majority of male patients were MSM. This study is similar with another study in Makassar Indonesia which was reported higher number of cases of syphilis among MSM (19). Previous study in six Indonesian cities reported data and analyses which indicate that MSM are at elevated risk for HIV infection in many low and middle income countries (20)(21).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of the 220 patients diagnosed with secondary syphilis in Indonesia, the majority of male patients were MSM. This study is similar with another study in Makassar Indonesia which was reported higher number of cases of syphilis among MSM (19). Previous study in six Indonesian cities reported data and analyses which indicate that MSM are at elevated risk for HIV infection in many low and middle income countries (20)(21).…”
Section: Discussionsupporting
confidence: 90%
“…Previous study in six Indonesian cities reported data and analyses which indicate that MSM are at elevated risk for HIV infection in many low and middle income countries (20)(21). There is signicant risk for increasing number of transmission between syphilis and HIV among MSM group (19,(22)(23). Therefore, it should be considered in patients diagnosed with…”
Section: Discussionmentioning
confidence: 99%
“…[5] The primary and secondary phases typically occur over a period of weeks to months, but the interval between the secondary and tertiary phases can last up to several years. [6,7] Syphilis and HIV often co-occur and mutually influence each other. Syphilitic ulcers can serve as a source of entry for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This was reported by the European Centre for Disease Prevention and Control (ECDC) in 2019, while the highest proportion of syphilis cases were in the age group of 25-34 years old 5 . The retrospective study conducted by Kusumawaty et al showed that the age group with the most syphilis patients in Makassar in 2017-2018 was between 21-30 years old (51.8%) 8 .…”
Section: Discussionmentioning
confidence: 99%